Rich vehicle routing with auxiliary depots and anticipated deliveries: An application to pharmaceutical distribution. (September 2019) - Kramer, Raphael; Cordeau, Jean-François; Iori, Manuel
Highlights: We introduce a rich vehicle routing problem arising in the field of pharmaceutical distribution. An simple and effective ILS algorithm is proposed. The impact of using auxiliary depots and anticipated deliveries on the routing costs is evaluated. Realistic and artificial instances containing up to 300 customers are solved. Abstract: We present and solve a rich vehicle routing problem based on a practical distribution problem faced by a third-party logistics provider, whose aim is to deliver pharmaceutical products to healthcare facilities in Tuscany. The problem is characterized by having multiple depots, a heterogeneous fleet of vehicles, flexible time windows, periodic demands, incompatibilities between vehicles and customers, a maximum duration for the routes, and a maximum number of customers per route. A multi-start iterated local search algorithm making use of several neighborhoods is proposed to solve the problem. The algorithm has been tested on a large number of instances and obtained good results, both on the real case study and on a number of artificially generated instances.